Menswear with a western theme - Gordon, John C. (photographer):::Creator::::::::::::
Men's clothing in a store. Jackets, hats, shirts, and cowboy boots are on display. The store's decor is inspired by the American West. Rifles hang from shelves. One animal hide sits atop the shelves. Antlers and wagon wheels also form part of the display.